2008
DOI: 10.1371/journal.pone.0003222
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Nuclear Genes Suggest that Stony Corals Are Monophyletic but Most Families of Stony Corals Are Not (Order Scleractinia, Class Anthozoa, Phylum Cnidaria)

Abstract: Modern hard corals (Class Hexacorallia; Order Scleractinia) are widely studied because of their fundamental role in reef building and their superb fossil record extending back to the Triassic. Nevertheless, interpretations of their evolutionary relationships have been in flux for over a decade. Recent analyses undermine the legitimacy of traditional suborders, families and genera, and suggest that a non-skeletal sister clade (Order Corallimorpharia) might be imbedded within the stony corals. However, these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
513
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(567 citation statements)
references
References 32 publications
47
513
7
Order By: Relevance
“…This analysis showed that all five genera and nine of ten families for which more than one taxon were tested formed monophyletic groups. However, of the seven suborders examined, only three-Meandriina, Poritiina and Dendrophylliinawere recovered unambiguously as clades, although only Dendrophylliina remains the only monophyletic suborder to emerge from recent studies (e.g., Fukami et al 2008;Arrigoni et al 2014a). …”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…This analysis showed that all five genera and nine of ten families for which more than one taxon were tested formed monophyletic groups. However, of the seven suborders examined, only three-Meandriina, Poritiina and Dendrophylliinawere recovered unambiguously as clades, although only Dendrophylliina remains the only monophyletic suborder to emerge from recent studies (e.g., Fukami et al 2008;Arrigoni et al 2014a). …”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 98%
“…Therefore, these genes are more informative for reconstructing deep coral phylogenies. Other than the 16S rDNA that established widespread subordinal non-monophyly Palumbi 1996, 1997;Le GoffVitry et al 2004), 12S rDNA, cytochrome b and cytochrome c oxidase subunit I (COI) were purposed for corals relatively early (Medina et al 1999;van Oppen et al 1999;Fukami et al 2000) and have been used for inferring large scleractinian trees effectively (Chen et al 2002;Fukami et al 2004bFukami et al , 2008Barbeitos et al 2010;Kitahara et al 2010bKitahara et al , 2013Stolarski et al 2011;Arrigoni et al 2012Arrigoni et al , 2014cHuang 2012;Huang andRoy 2013, 2015;Marcelino et al 2013;Curnick et al 2015; Fig. 4.1).…”
Section: The Rise Of Molecular Phylogenetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model included three random effects: faunal break, clade [49] and suborder [50]; the latter two were nested and included to account for any phylogenetic non-independence that was not explicitly captured within sexuality or genus age [51]. We investigated all combinations of main effects and interaction terms that were judged to be biologically feasible (see the electronic supplementary material, methods (g)).…”
Section: (D) Species Traitsmentioning
confidence: 99%